THE INFLUENCE OF HUMAN RESOURCE COMPETENCE AND THE USE OF INFORMATION TECHNOLOGY ON THE QUALITY OF VILLAGE GOVERNMENT FINANCIAL REPORTING WITH AN INTERNAL CONTROL SYSTEM AS A MODERATION VARIABLE : (A Study in Tungkal Ilir District, Bram Itam District, Betara District, West Tanjung Jabung Regency) - Andi Juhanesa Putra; Ilham Wahyudi; Rico Wijaya Z. (Transpublika Publisher, 2024)
This research aims to determine and test the influence of human resource competence and the use of information technology on the quality of village financial reports with an internal control system as moderation. The research population is village officials who are responsible for managing village funds in Tungkal Iir, Bram Itam and Betara Districts, West Tanjung Jabung Regency with a sample of 4 people from 22 villages. The research method is a quantitative method with Smart-PLS analysis. The research results concluded: (1) human resource competency has an influence on the quality of village financial reports in Tungkal Ilir, Bram Itam and Betara Districts, Tanjung Jabung Regency; (2) The use of information technology has an influence on the quality of village financial reports in Tungkal Ilir, Bram Itam and Betara Districts, West Tanjung Jabung Regency; (3) the internal control system is not able to moderate the competence of human resources on the quality of village financial reports in Tungkal Ilir, Bram Itam and Betara Districts, West Tanjung Jabung Regency and (4) the internal control system is not able to moderate the use of information technology on the quality of sub-district village financial reports.